Cumulative ecological risk and academic adjustment in freshmen: mediation by problematic mobile phone use and moderation by self-control - Yu, Meiqi; Xia, Yanyu; Ye, Weihao; Zhang, Jinjun; Gu, Yanan (Frontiers in Psychology, 2025)
IntroductionPrevious research has shown that multiple ecological risks, including family, school, peer, and societal risk factors, significantly affect students' academic adjustment. Based on Ecological systems theory, the present study explored the effect of cumulative ecological risk (CER) on freshmen's academic adjustment, the mediating role of problematic mobile phone use (PMPU), and the moderating role of self-control.MethodsA total of 2,962 freshmen, of which 1,564 were male (52.80%), participated in this study and completed the Cumulative Ecological Risk Questionnaire, Chinese Version of the College Students' Problematic Mobile Network Usage Behavior Scale, Self-Control Scale, and Chinese Version of the Undergraduate's Learning Adjustment Test.ResultsThe results showed that (1) there were significant correlations between CER, PMPU, self-control, and academic adjustment; (2) CER significantly negatively predicted freshmen's academic adjustment; (3) PMPU had a mediating effect between CER and academic adjustment; and (4) self-control moderated the effects of CER on both PMPU and academic adjustment.DiscussionThese results provide a theoretical and empirical basis for formulating appropriate countermeasures to enhance the academic adjustment of freshmen who face various ecological risks.